Phenotypic stability for seed yield and related traits in Trombay mustard genotypes under North western Himalayas (Journal of Oilseed Brassica, 2026)
The present study was conducted to evaluate different Trombay mustard genotypes for their stability in yield performance under varied agro-climatic conditions of the state. Five promising Trombay mustard genotypes viz., TM-136, TM-172, TM-204, TM-215 and TM-224 were evaluated along with three checks viz. Kranti, RL-1359 and RCC-4 under eleven environments spread over different agro-climatic zones of Himachal Pradesh during Rabi 2012-13 to 2015-16, for stability parameters with respect to four characters such as plant height (cm), number of siliquae per plant, maturity duration (days) and seed yield (kg/ha). Pooled analysis of variance for stability revealed significant differences among different genotypes for plant height, days to maturity and seed yield indicating that the genotypes selected possessed significant variation for these characters. Significant mean squares due to environments confirmed that the environments selected were variable in nature which influenced the expression of all the characters under study. Significant mean squares for genotype x environment (g x e) interaction revealed the differential response of Trombay mustard genotypes over environments for plant height, days to maturity and seed yield. The partitioning of environment + (genotype x environment) mean squares into different components revealed that the linear component of environment appeared to be highly significant for all the characters under study which indicated large macro-environmental differences in four years for these characters. All the eight genotypes were tested for three stability parameters viz. mean, bi and S2di. Out of eight genotypes, only one genotype viz. TM-224 was identified to be stable for dwarf plant height. The genotypes such as TM-172, Kranti (national check) and RL-1359 (zonal check) exhibited higher siliquae per plant than the overall population mean and stability for this character. The two genotypes viz., TM-136 and Kranti exhibited stability for early maturity while none of the genotypes exhibited stability for seed yield across the varied environments. The check Kranti appeared to be average in performance and stability for seed yield though, the values were slightly lower than the population mean. Thus, these genotypes may be involved in breeding programme to develop high yielding and stable genotypes over different environments or could be recommended for cultivation across the environments.